(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
Comparative studies of retted jute fiber, jute cuttings and jute caddis were carried out in producing dissolving and paper grade pulp. Fiber length of jute fiber was longer than jute cutting and caddis. Klason lignin content was lower and α-cellulose content higher in jute fiber than cuttings and caddis. Extractives content in caddis was higher than jute fiber and cuttings. Pulping of these raw materials was done in soda-anthraquinone process. Higher pulp yield and lower kappa number was observed in jute fiber than that of jute cuttings and caddis. Jute fiber pulp showed better papermaking properties than jute cuttings and caddis. The tear index of these raw materials was similar to softwood. The bleachability of jute fiber pulp was also better than that of cuttings and caddis. These three raw materials were also evaluated in producing dissolving pulp by prehydrolysed kraft process. Pulp yield and bleachability was higher and kappa number lower for jute fiber than jute cuttings and caddis, but α-cellulose, S10 and S18 values and viscosity were almost similar in these three raw materials. Keywords: Jute fiber, Jute cuttings, Jute caddis, Paper grade pulp, Dissolving pulp Bangladesh J. Sci. Ind. Res. 42(4), 425-434, 2007